Distinct and enhanced hygienic responses of a leaf-cutting ant toward repeated fungi exposures - Goes, Aryel C. [UNESP]; Kooij, Pepijn W. [UNESP]; Culot, Laurence [UNESP]; Bueno, Odair C. [UNESP]; Rodrigues, Andre [UNESP] (Wiley, 2022)
Leaf-cutting ants and their fungal crops are a textbook example of a long-term obligatory mutualism. Many microbes continuously enter their nest containing the fungal cultivars, destabilizing the symbiosis and, in some cases, outcompeting the mutualistic partners. Preferably, the ant workers should distinguish between different microorganisms to respond according to their threat level and recurrence in the colony. To address these assumptions, we investigated how workers of Atta sexdens sanitize their fungal crop toward five different fungi commonly isolated from the fungus gardens: Escovopsis sp., Fusarium oxysporum, Metarhizium anisopliae, Trichoderma spirale, and Syncephalastrum sp. Also, to investigate the plasticity of these responses toward recurrences of these fungi, we exposed the colonies with each fungus three times fourteen days apart. As expected, intensities in sanitization differed according to the fungal species. Ants significantly groom their fungal crop more toward F. oxysporum, M. anisopliae, and Syncephalastrum sp. than toward Escovopsis sp. and T. spirale. Weeding, self-, and allogrooming were observed in less frequency than fungus grooming in all cases. Moreover, we detected a significant increase in the overall responses after repeated exposures for each fungus, except for Escovopsis sp. Our results indicate that A. sexdens workers are able to distinguish between different fungi and apply distinct responses to remove these from the fungus gardens. Our findings also suggest that successive exposures to the same antagonist increase hygiene, indicating plasticity of ant colonies' defenses to previously encountered pathogens.
Keywords: Atta sexdens; disease; pathogens; secondary exposures; social immunity